The Influence Of Customers’ Perception And Attitudes Toward Customer Purchase Intention At Gramedia Lembuswana, Samarinda - Hanif Adinugroho Widyanto; Tubagus Achmad Rachmad Saleh (FIRM Journal of Management Studies, 2018)
This research aims to find out the influence between customers’ perceptions and attitude toward customerpurchase intention at Gramedia Lembuswana, Samarinda that is experiencing a slowdown in sales growth.Factors examined are extrinsic factors which include perceived price, advertisement, and store image;intrinsic factors which include perceived quality, perceived risk and perceived value; and customer’attitudes which include trust, and familiarity. All responses were collected by using questionnaire with apurposive sampling method. The methodology used in this research is quantitative by utilizing themultiple regression analysis. The research population are people who have purchased items at GramediaLembuswana. Likert scale was used on 165 random respondents of the research. The result shows thatperceived value, advertisement, store image, trust, and familiarity have significant influence towardintention to purchase, while perceived quality, perceived risk, and perceived price do not have asignificant influence toward customer purchase intention. Finally, all the independent variables are foundto have simultaneously significant impact toward customer purchase intention with an adjusted R squarevalue of 0.467.